Diseño y construcción de un banco para la medición de pérdidas por fricción en tuberías PVC y accesorios (2022)
The purpose of this project is to Abstract provide the Antonio Nariño University Hydraulics Laboratory with a test bench to measure friction losses in PVC pipes and other accessories that is useful for students' practical learning. It was carried out through a group brainstorming methodology, made up of the teacher and students in charge of this project, where the characterization and selection of different design variables was carried out. A bibliographic search was also carried out, obtaining a significant contribution in terms of its design and construction, taking into account each of the suggested recommendations to carry out a correct elaboration and functionality of the equipment. For the design of this, the SolidWorks software was implemented and for the calculations of the energy losse s, the Excel tool was used for each Pipe Trajectory to facilitate obtaining them. However, the calculation of energy losses by accessories was also carried out manually, illustrating the equations used for the reader.